Comparative analysis of methodologies applied to the demarcation of the basin of Rio Doce - RN - Costa, Franklin Roberto da; Souza, Raquel Franco de; Silva, Sebastião Milton Pinheiro da (Sociedade & Natureza, 2016)
The watershed is considered a geographical clipping important for environmental planning. Its correct delineation allows appropriate planning with the needs of society. In this sense, the present work aims to carry out a comparative analysis of visual automatic boundaries performed with the programs TauDEM, SAGA and TERRAHIDRO, as well as the delimitation by visual analysis, with the official boundaries of the SEMARH-RN and ANA (ottobacia 05 level), aiming to redefine and update the limits of the basin of Rio Doce/RN. To do the demarcation used the terrain elevation data of the database geomorphometrics of Brazil, TOPODATA, hydrography of topographical maps of SUDENE, in scale 1:100,000, the Google Earth images, worked in SIGs QGIS 2.14 “Essen” and the Terraview hydro 0.4.1. The results showed that the delimitation and automatic visual analysis using the TERRAHIDRO Platform identified the basin boundaries in their flattened areas. Already the TauDEM and the SAGA identified a palaeochannel of Doce river, directing, so the mouth of the basin point. It is understood that the TERRAHIDRO presented the best result for the demarcation of the basin by its use to basin to medium and large scales.